The Role Analysis of Waste Bank in Improving the Community's Creative Economy (Study at Ketumbar Pamulang Waste Bank) - Gunartin Gunartin; Edi Mulyanto; Denok Sunarsi (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
The research objective with the title "Analysis of the Role of Waste Banks to Improve the Creative Economy of the Community (Study at the Pamulang Garbage Bank) wants to know and describe the role of waste banks in an effort to improve the community's economy. Research with the object of the Ketumbar waste bank which is located at RW 18 Banda Baru Pamulang, South Tangerang uses a descriptive qualitative approach to explain the existing phenomena or symptoms. The waste bank has a big enough role in dealing with waste problems that have not yet been handled effectively and efficiently. It is hoped that the presence of a waste bank will be able to contribute to reducing the volume of waste as well as improving the creative economy of the community. The research, which uses researchers as its instrument, by conducting data collection techniques through interviews and document studies, determines the coordinator of the Benda Baru waste bank and his three teams as the key informants, which are the primary sources of information. The results show that the role of the waste bank has been able to improve the creative economy of the community but has not been optimal because what has been done is only as a container, the distributor has returned to the stall, has not yet reached the recycling development process so as to produce competitive production if marketed because it is constrained by the craftsmen who have creative power and marketing the creations of used goods craftsmen. This is because people still look down on used goods even though they have been recycled and the government's attention is not yet optimal in opening distribution channels for creative waste products. So the role of the new garbage nk plays a role as an intermediary for the community with used goods collectors stalls.